Transformative Leadership in Educational Change Management: Enhancing Teacher Readiness for Centrally-Based E-Report Card Implementation - Ummul Khoiroh; Tiara Nurul Annisa’; Ummi Hani; Toyyibatul Mukminatus S; Juwita; Abu Hasan Agus R; Mohammad Bahrul Ulum (Al-Qalam Institue, 2026)
This study aims to analyze the role of transformational leadership in shaping teacher readiness for the implementation of a centrally mandated e-Report system as part of digital education policy. Employing a qualitative research design, data were collected through in-depth interviews, observations, and document analysis involving school principals and teachers. The findings indicate that successful implementation of the e-Report system is not determined solely by technological readiness, but is strongly influenced by leadership practices that develop a shared vision, strengthen teacher commitment through motivation and organizational regulation, and enhance professional capacity through mentoring and role modeling. The study also reveals that organizational challenges, including technological limitations and disparities in digital literacy, are managed through open communication and adaptive, collaborative problem-solving strategies. Teacher readiness emerges as a form of professional awareness grounded in shared responsibility rather than mere administrative compliance. This study implies that transformational leadership functions as a critical mediating mechanism between top-down policy directives and school-level practice. It highlights the importance of relational, participatory, and context-sensitive leadership approaches in sustaining digital assessment reforms and strengthening educational governance.